The existence of solutions for four-point coupled boundary value problems of fractional differential equations at resonance - Zou, Y.; Liu, Lishan; Cui, Y. (Hindawi Publishing Corporation, 2014)
A four-point coupled boundary value problem of fractional differential equations is studied. Based on Mawhin's coincidence degree theory, some existence theorems are obtained in the case of resonance. © 2014 Yumei Zou et al.